ANALYSIS OF SIZE AND SENSOR ON SUN TRACKER DUAL AXIS TETRAHEDRON USING FUZZY LOGIC (Science and Technology (SciTech), 2023)
Solar energy is optimally obtained by solar cells when the solar cells are perpendicular to the sun's position, so a sun tracker is needed to track the sun precisely. This study compares the electrical energy obtained from the proposed dual-axis sun tracker system with different size tetrahedron geometries and using a phototransistor sensor with previous studies using a tetrahedron geometry with a more obtuse triangle size and using an LDR sensor. A solar module equipped with a sun tracker that applies the Fuzzy logic method has been developed to improve the performance of both sun trackers. The voltage and current values ​​of the solar modules are used as input for the Fuzzy algorithm. The results showed that the sun tracker in the proposed study obtained an average voltage value of 39.58% greater than the sun tracker in previous studies. The average current value in the proposed sun tracker research is 39.56% greater than the previous sun tracker research. The value of the electrical energy generated in a solar module using a sun tracker is directly proportional to the value of the voltage and current generated, that is, if the voltage and current values ​​are large, the value of the electrical energy obtained will also be greater. The average electrical energy yield of solar modules using a sun tracker like the research proposed is 60.55% greater than solar modules using a sun tracker from previous research.